Determinants of survival of the bovine blastocyst to cryopreservation stress: treatment with colony stimulating factor 2 during the morula-to-blastocyst transition and embryo sex - Froylan Sosa; Jeremy Block; Yao Xiao; Peter J. Hansen (CABI Agriculture and Bioscience)
Abstract Background Colony-stimulating factor 2 (CSF2) is an important maternal regulator of embryonic development. Earlier research indicates that CSF2 can regulate genes involved in cellular stress responses and block apoptosis. Here, we tested whether addition of 10 ng/mL CSF2 at day 5 of development would increase the survival of blastocysts harvested at day 7 and subjected to vitrification. Additional objectives were to determine whether embryo sex affected survival or whether effects of CSF2 interacted with sex. Results Survival after vitrification was measured as the percent of warmed blastocysts that re-established a blastocoele after culture and that underwent hatching from the zona pellucida. In the first experiment, blastocysts were vitrified, warmed, cultured for 24 h, and DNA embryo sexing performed by PCR. There was no effect of CSF2, sex, or the interaction on the percent of blastocysts that re-expanded or that were hatching or hatched. In the second experiment, vitrified blastocysts were warmed and cultured for 24, 48, and 72 h. Treatment with CSF2 increased (P = 0.021) the percent of blastocysts that re-expanded as compared to the vehicle group (overall, 77.8 ± 4.7% vs 73.3 ± 4.7%). Percent re-expansion was highest at 24 h and declined slightly thereafter (P = 0.024). Although the interaction was not significant, the effect of CSF2 was greater at 48 and 72 h than at 24 h because CSF2 reduced the incidence of embryos collapsing after re-expansion. Furthermore, the proportion of re-expanded blastocysts at 24 h that experienced blastocoel collapse by 72 h was lower (P = 0.053) for CSF2 (3.6%; 7/195) than for vehicle (8.2%; 16/195). The percent of warmed blastocysts that were hatching or hatched increased with time (P < 0.0001) but there was no effect of CSF2 or the interaction with time on hatching. Conclusion Treatment with CSF2 from day 5 to 7 of development did not cause a significant effect on the percent of blastocysts that re-established the blastocoele after 24 h of culture but CSF2 reduced the collapse of the blastocoele that occurred for a portion of the embryos that had experienced re-expansion at 24 h. Thus, CSF2 can provide protection to a proportion of blastocysts from cryodamage caused by vitrification. Further work is needed to evaluate whether CSF2 increases survival of vitrified blastocysts after embryo transfer.